‘Lembranças da Terra’. Notas para uma etnografia da produção de artesanato nas cidades do Mindelo e da Praia, Cabo Verde - Rovisco, Eduarda (Trabalhos de Antropologia e Etnologia, 2020)
Between 1977 and 1997, Mindelo and Praia hosted the Centro Nacional de Artesanato (CNA, National Handicraft Centre) and its regional delegation, two State run bodies decisive in the making of Cape Verdean folk art during the First Republic. These two towns now have a remarkable number of craftsmen, and are the major production centres in the field. Drawing on materials resulting from a retrospective ethnography of CNA and also on research into these towns’ current handicraft production and trade, this paper contains a doubly comparative exercise (synchronous and diachronic) in search of continuities and rupture.